Study of charged particle activation analysis (II): Determination of boron concentration in human blood samples. (October 2020) - Ikebe, Y.; Oshima, M.; Bamba, S.; Asai, M.; Tsukada, K.; Sato, T.K.; Toyoshima, A.; Bi, C.; Seto, H.; Amano, H.; Kumada, H.; Morimoto, T.
Abstract: Boron Neutron Capture Therapy (BNCT) is a radiotherapy for the treatment of intractable cancer. In BNCT precise determination of 10 B concentration in whole blood sample before neutron irradiation of the patient, as well as accurate neutron dosimetry, is crucial for control of the neutron irradiation time. For this purpose ICP-AES and neutron induced prompt γ-ray analysis are generally used. In Ibaraki Neutron Medical Research Center (iNMRC), an intense proton beam will be accelerated up to 8 MeV, which can also be used for Charged Particle Activation Analysis (CPAA). Thus, in this study, we apply the CPAA utilizing the proton beam to non-destructive and accurate determination of 10 B concentration in whole blood sample. A CPAA experiment is performed by utilizing an 8 MeV proton beam from the tandem accelerator of Nuclear Science Research Institute in Japan Atomic Energy Agency. The 478 keV γ-ray of 7 Be produced by the 10 B(p, α) 7 Be reaction is used to quantify the 10 B in human blood. The 478 keV γ-ray intensity is normalized by the intensities of the 847 keV and 1238 keV γ-rays of 56 Co originating from Fe in blood. The normalization methods were found to be linear in the range of 3.27 μg 10 B/g to 322 μg 10 B/g with correlation coefficients of better than 0.9999. Highlights: A charged particle activation utilizing an 8 MeV proton beam is applied for the determination of 10 B in human blood. The 478 keV γ-ray of 7 Be produced by the 10 B(p, α) 7 Be reaction is used to quantify the 10 B. 56 Fe can be used as a reference to determine the concentration of 10 B in whole blood samples. The 511 keV γ-ray background can be reduced effectively by cooling of more than 5 h. Optimization of irradiation and measurement conditions will be performed to reduce analysis time and uncertainty.